Rancang Bangun Sistem Penilaian Tes Essai Berbasis Web Di Testing Center UNM - Nur Fadilah; Satria Gunawan Zain (Sakura Publisher, 2024)
This research is a web-based assessment system design that aims to build a web essay grading system at the UNM Testing Center. This study utilizes Research and Development (RnD) methods in the field of software engineering and uses the Prototype model in the system development process, as well as conducting software quality checks based on ISO 9126 standards involving four main aspects, namely functionality, reliability, portability, and usability. The result of this study is a web-based essay test scoring system at the UNM Testing Center. The results of the examination of the sub-characteristics of the accessory and suitability functions showed a conformity rate of 85%. For part security characteristics, the system has been tested and free of malware, website blacklisting, injected SPAM, defacement, and SQLInjection. In terms of reliability, the system is considered feasible with a feasibility percentage of 98.87%. The portability test showed a feasibility rate of 96.33%, while the usability test showed a feasibility rate of 81.43%.